Low hanging fruit: harvesting the potential of DNA-free genome editing in red raspberry (Rubus idaeus) - Creeth, Ryan; Thompson, Andrew J.; Kevei, Zoltan (Springer, 2026)
Red raspberry (Rubus idaeus) is a high-value crop species coveted for its flavour and health benefits. Annual global production is increasing year-on-year and currently exceeds 900,000 metric tonnes. Despite this popularity, raspberry breeding remains laborious and time-consuming, limiting trait improvement and new cultivar development. Genome editing offers a solution to increase the speed and accuracy of plant breeding while reducing costs. The use of DNA-free genome editing, which utilises ribonucleoprotein complexes without transgenic introgression, enables trait enhancement without genetic modification (GM). This is desirable due to enduring negative public sentiment toward GM foods and legislative change in regions such as England. However, there is a large research gap applying DNA-free genome editing methods to raspberry. Non-transgenic genetic improvement in raspberry would be a breeding paradigm shift, enabling trait improvements including increased firmness, improved flavour, disease resistance and optimised plant architecture. This review focuses on the process of DNA-free genome editing, from protoplast source to plant recovery, incorporating new research demonstrating the feasibility of raspberry protoplast isolation and DNA-free editing. We explore remaining technical challenges including the elucidation of protoplast regeneration and the optimisation of editing efficiency. We advocate for better standardisation, integration and clarity of regeneration methods to effectively harvest the opportunities of DNA-free genome editing in crop species.
Keywords: CRISPR-Cas9; Genome editing; Rubus idaeus; DNA-free; RNPs; Protoplast regeneration; 30 Agricultural, Veterinary and Food Sciences; 3008 Horticultural Production; Genetics; Biotechnology; Plant Biology & Botany; 3001 Agricultural biotechnology; 3108 Plant biology